2010
DOI: 10.1007/s10565-009-9148-4
|View full text |Cite
|
Sign up to set email alerts
|

l-carnitine modulates blood platelet oxidative stress

Abstract: The oxidative stress induced by acute exertion may interfere with blood platelet activation. The beneficial effect of L-carnitine (gamma-trimethylamino-beta-hydroxybutyric acid) on oxidative stress in blood platelets has not been fully investigated; however, different studies indicate that this compound modulates platelet functions. The aim of our study was to assess the effects of L-carnitine on platelet activation and oxidative/nitrative protein damage (determined by the levels of protein carbonyl groups, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
1
15
0
1
Order By: Relevance
“…17 The excessive production of NO from iNOS can react rapidly with superoxide anion to cause the formation of the highly reactive peroxynitrite (ONOO−), which is involved in the oxidation and nitration of fibrinogen (a key protein in the coagulation cascade) and plasminogen (the main protein of fibrinolysis process). 18 In agreement with this, mutant mice lacking iNOS were resistant to LPSinduced mortality. 19 In contrast, the blockade of all isoforms of NOS with L-NAME did not protect from the lethal septic shock, suggesting that eNOS may counteract the negative effect of iNOS.…”
Section: Discussionsupporting
confidence: 59%
“…17 The excessive production of NO from iNOS can react rapidly with superoxide anion to cause the formation of the highly reactive peroxynitrite (ONOO−), which is involved in the oxidation and nitration of fibrinogen (a key protein in the coagulation cascade) and plasminogen (the main protein of fibrinolysis process). 18 In agreement with this, mutant mice lacking iNOS were resistant to LPSinduced mortality. 19 In contrast, the blockade of all isoforms of NOS with L-NAME did not protect from the lethal septic shock, suggesting that eNOS may counteract the negative effect of iNOS.…”
Section: Discussionsupporting
confidence: 59%
“…Following treatment with ONOO - , NT expression was raised in CHD patients, but not in healthy donors. Recent data has demonstrated that some supplements such as L-carnitine can protect platelets against the nitrating effects of ONOO - [43] and it is possible that platelet levels of endogenous antioxidants were higher in healthy donors. Similarly, the O 2 -• generating X/XO system or XO alone, which would likely generate O 2 -• anions, also caused a small increase in platelet NT expression in CHD patients, likely through an interaction with platelet-derived • NO.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lcarnitine has been proposed as a potential adjuvant treatment to improve anaemia, thrombocytopenia, leukopenia and immunological function. [68][69][70][71][72][73] In a recent study, L-carnitine added to Peg-IFN-α plus ribavirin led to less decrease of platelet count during antiviral therapy. 74 Some studies indicate that L-carnitine modulates platelet functions and production through antioxidant mechanisms and the inhibition of the arachidonic acid cascade.…”
Section: L-carnitinementioning
confidence: 99%